The impact of environmental accidents on the green apparel purchase behavior of Generation Z - Liu, Lixian; Zhang, Wenwen; Li, Hao; Zheng, Zeyu (Frontiers in Psychology, 2024)
This study aims to explore the impact of environmental accidents on the purchase behavior of Generation Z toward green apparel. Based on an integrated theoretical framework combining the Theory of Planned Behavior and the Norm Activation Theory, this study conceptualized the dimensions of environmental accidents that influence Generation Z's purchase behavior through focus groups and questionnaires. Data collected is analyzed using SPSS software, and the research hypotheses were tested using structural equation modeling. Findings reveal that the scale (H12=0.545), the degree of suddenness (H18=0.357), nature of the effect (H14=0.295), and duration (H17=0.289) of the environmental accident have varying degrees of influence on the awareness of consequences, behavioral attitudes, subjective norms, and perceived behavioral control of Z Generation's green clothing purchasing. Furthermore, the scale of environmental accidents significantly impacts perceived behavioral control, which in turn significantly affects Generation Z's green apparel purchase intention (H3=0.5). Additionally, the research confirms the applicability of the Norm Activation Theory in examining Generation Z's green apparel purchase behavior.